Entrepreneurial Interventions for crisis management: Lessons from the Covid-19 Pandemic's impact on entrepreneurial ventures. (1st April 2022) - Krishnan, Commander S. Navaneetha; Ganesh, L.S.; Rajendran, C.
Highlights: A crisis can either cause failure or provide new opportunities for Entrepreneurial Ventures (EVs). The behaviour of EVs during a crisis is presented using a Phenomenon Structure Diagram (PSD). Entrepreneurial ventures employ a combination of Actions (EAs), Orientations (EOs), with Supports (ESs) to manage crises. The combination of EAs and EOs with ESs is referred to as Entrepreneurial Interventions. Entrepreneurial Interventions can be a crisis management strategy. Abstract: This article investigates both the negative and positive impacts of a crisis on Entrepreneurial Ventures. The behaviour of Entrepreneurial Ventures during the COVID-19 pandemic crisis is studied by undertaking a Systematic Literature Review (SLR) using Bibliometrics of 154 related publications. After analyzing the literature, the behaviour of Entrepreneurial Ventures during the crisis is synthesized and presented as a Phenomenon Structure Diagram, which highlights a combination of Entrepreneurial Actions (EAs) and Entrepreneurial Orientations (EOs), with Entrepreneurial Supports (ESs) employed by them to manage the crisis. This combination of EAs and EOs with ESs is contingent on the surrounding environment, and they aid in minimizing the risk of failure as well as leverage new opportunities. We propose and develop a conceptual model that a combination of EAs and EOs with ESs, referred to as Entrepreneurial Interventions, can better manage a crisis or disaster and improve organizational resilience. This multi-disciplinary study contributes towards theory development that Entrepreneurial Interventions can be made as a crisis and disaster management strategy.